Acute Neurofilament Light Chain Plasma Levels Correlate With Stroke Severity and Clinical Outcome in Ischemic Stroke Patients - Nielsen, Helle H.; Soares, Catarina B.; Høgedal, Sofie S.; Madsen, Jonna S.; Hansen, Rikke B.; Christensen, Alex A.; Madsen, Charlotte; Clausen, Bettina H.; Frich, Lars Henrik; Degn, Matilda; Sibbersen, Christian; Lambertsen, Kate L. (Frontiers in Neurology, 2020)
Background: Ischemic stroke causes increased blood-brain barrier permeability and release of markers of axonal damage and inflammation. To investigate diagnostic and prognostic roles of neurofilament light chain (NF-L), we assessed levels of NF-L, S100B, interleukin-6 (IL-6), E-selectin, vascular endothelial growth factor-A (VEGF-A), vascular cell adhesion molecule-1 (VCAM-1), and intercellular adhesion molecule-1 (ICAM-1) in patients with acute ischemic stroke or transient ischemic attack (TIA) and healthy controls. Methods: We studied neurofilament (NF) expression in 2 cases of human post-mortem ischemic stroke, representing infarcts aged 3 to >7 days. In a prospective study, we measured plasma NF-L and inflammatory markers <8 hours of symptom onset and at 72 hours in acute ischemic stroke (n=31), TIA (n=9), and healthy controls (n=29). We assessed whether NF-L, S100B, and IL-6 were associated with clinical severity on admission (Scandinavian Stroke Scale, SSS), diagnosis of ischemic stroke versus TIA, and functional outcome at 3 months (modified Rankin Scale, mRS). Results: NF expression increased in ischemic neurons and in the infarcted brain parenchyma after stroke. Plasma NF-L levels were higher in stroke patients than TIA patients and healthy controls, but IL-6 levels were similar. Higher acute NF-L levels were associated with lower SSS scores at admission and higher mRS scores at 3 months. No correlation was observed between NF-L and S100B, NF-L and IL-6, nor between S100B or IL-6 and SSS or mRS. Compared to controls, stroke patients had significantly higher VEGF-A and VCAM-1 at <8 hours that remained elevated at 72 hours, with significantly higher VEGF-A at <8 hours; ICAM-1 was significantly increased at <8 hours, while S100B and E-selectin were unchanged. Conclusions: Plasma NF-L levels, but not IL-6 and S100B, were significant predictors of clinical severity on admission and functional outcome at 3 months. Plasma NF-L is a promising biomarker of functional outcome after ischemic stroke.